Strategi Toko Kue Ajm Cake Di Rote Dalam Meningkatkan Pendapatan - Permata, Tri Wahyuni Indah; Malelak, Aprilmus Jefian (JCOMENT (Journal of Community Empowerment), 2023)
This research is motivated by the decline in income at AJM Bakery's cake shop during 2022, the lack of strategies owned by AJM Bakery's cake shop and the decreasing number of consumers. This study aims to describe the strategy of increasing revenue for the AJM Bakery Shop Cake Business Solution to increase bread sales at the Shinta Bakery Shop Cake Business dur The research method used is descriptive qualitative. The data collection instrument used interview and documentation guidelines. Test the validity of the data using source triangulation and technical triangulation. The data analysis technique uses condensation data, display data, and conclusion drawing/verification. The results showed that the products in the Cake Shop AJM Bakery business were in the form of blocks, rounds, ovals, triangles, squares, while the product features at the AJM Bakery Cake Shops did not have special features. The prices set at the AJM Bakery Cake Shop are relatively expensive compared to other cake shops. The location of the AJM Bakery Cake Shop business can be said to be quite strategic and makes it easy for consumers from any region to reach this store, because the AJM Bakery Cake Shop is right in front of the main highway. Promotional promotions carried out by the AJM Bakery Cake Shop only use banners installed in front of the store as a promotional medium.